ВИЗНАЧЕННЯ ОПТИМАЛЬНИХ ХАРАКТЕРИСТИК ВИСОКОВОЛЬТНОЇ ЕЛЕКТРОРОЗРЯДНОЇ СИСТЕМИ ДЛЯ РЕАЛІЗАЦІЇ ТЕХНОЛОГІЇ ЕЛЕКТРОІМПУЛЬСНОГО СИНТЕЗУ НАНОВУГЛЕЦЮ - Вінниченко , Д.В. (Інститут електродинаміки НАН України, Київ, 2014)
On the basis of systematization the experimental results the optimal parameters and modes of high-voltage electric discharge systems that implement the new technology of electro-pulse synthesis of nanocarbon from gaseous carbonaceous raw materials are determined. The electrical processes in the plasma channel of electrical discharge in propane were researched. Values of the breakdown voltage and the operating one as well as current-voltage characteristics of the discharge mode of nanocarbon synthesis of gaseous hydrocarbons were experimentally determined. References 9, tables 2, figures 4.